Functional Outcomes of Cochlear Implantation in Children with Bilateral Cochlear Nerve Aplasia - Goun Choe; Young Seok Kim; Seung-Ha Oh; Sang-Yeon Lee; Jun Ho Lee (Medicina, 2022)
Background and Objectives: Many otologists face a dilemma in the decision-making process of surgical management of patients with cochlear nerve (CN) aplasia. The goal of this study is to provide fresh evidence on cochlear implantation (CI) results in patients with CN aplasia. Materials and Methods: We scrutinized functional outcomes in 37 ears of 21 children with bilateral CN aplasia who underwent unilateral or bilateral CI based on cross-sectional and longitudinal assessments. Results: The Categories of Auditory Performance (CAP) scores gradually improved throughout the 3-year follow-up; however, variable outcomes existed between individuals. Specifically, 90% of recipients with a 1-year postoperative CAP score ≤1 could not achieve a CAP score over 1 even at 3-year postoperative evaluation, while the recipients with a 1-year postoperative CAP score >1 had improved auditory performance, and 72.7% of them were able to achieve a CAP score of 4 or higher. Meanwhile, intraoperative electrically evoked compound action potential was not correlated with postoperative CAP score. Conclusions: Our results further refine previous studies on the clinical feasibility of CI as the first treatment modality to elicit favorable auditory performance in children with CN aplasia. However, special attention should be paid to pediatric patients with an early postoperative CAP score ≤1 for identification of unsuccessful cochlear implants and switching to auditory brainstem implants.